Angiotensin-Converting Enzyme Insertion/Deletion (ACE I/D) Gene Polymorphism as a Risk Factor for Essential Hypertension - Kuswara, Hasna Nurazizah; Nauphar, Donny; Sari, Ariestya Indah Permata (GHMJ (Global Health Management Journal), 2024)
Background: Hypertension is the leading cause of death globally due to its complications, including coronary heart disease and stroke. In 2018, hypertension cases in West Java were the second highest among all populations in Indonesia. Genetics is one of the unmodifiable risk factors for hypertension. Angiotensin-converting enzyme insertion/deletion (ACE I/D) gene polymorphism could affect ACE production in the renin-angiotensin-aldosterone system (RAAS), which is linked to the regulation of blood pressure. Aims: To analyze ACE I/D gene polymorphism as a risk factor for hypertension in Cirebon. Methods: An observational analysis with a case-control design was used in this study. Blood samples were collected from 30 hypertensive patients and 30 healthy individuals at Talun Health Center. DNA extraction was performed to evaluate polymorphisms using ARMS-PCR. Statistical analyses, including the Chi-square test, Fisher’s exact test, Mann-Whitney, and Kruskal-Wallis test, were conducted to compare the case and control groups. The odds ratio was calculated to see the risk of the assessed variables, including genotype, allele frequency, and the presence of ACE I/D gene polymorphism. Results: In the case group, the frequency of the II genotype was 2 (6.7%), the ID genotype was 25 (83.3%), and the DD genotype was 3 (10.0%). In the control group, the frequency of the II genotype was 2 (6.7%), the ID genotype was 26 (86.7%), and the DD genotype was 2 (6.7%). Statistically, there was no significant association between ACE I/D gene polymorphisms in essential hypertension patients and healthy people (p=0.500; OR=1.556; 95% CI=0.241-10.049). Conclusion: ACE I/D gene polymorphism was not significantly associated with essential hypertension in Cirebon, West Java, Indonesia.    Received: 25 September 2024  |  Reviewed: 21 October 2024  |  Revised: 23 November 2024  |  Accepted: 30 November 2024.